Laughing is thinking and thinking is laughing: The brain as a zygomatic muscle - Marín-Casanova, José Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
A philosophy of laughter in the double sense of the genitive is attempted. The objective sense is the usual one in the history of thought: the common opinion is to consider humour as the other of thought. Paradigmatically, philosophy, as metaphysics, would be the agelastic intellectual position par excellence: the zero degree of humour. However, interpreting the genitive in a subjective sense, laughter reveals itself as thought, and thought as the continuation of laughter through the brain as zygomatic muscle. Thought and laughter expand reality. The sense of humour shows itself to be perhaps the genuine philosophical sense.